Can carbonated water support weight loss? - Akira Takahashi (BMJ Nutrition, Prevention & Health)
Background Carbonated water has been reported to induce satiety, gastric motility and lower serum glucose concentrations, but the mechanisms remain unclear.Methods This report explores the physiological effects of carbonated water, referencing a study published in 2004 on the mechanisms of hypoglycaemia induced by haemodialysis.Results Upon consumption of carbonated water, carbon dioxide (CO2) is absorbed into the bloodstream, and converted into bicarbonate by the enzyme carbonic anhydrase in erythrocytes. This process increases intracellular pH, stimulating anaerobic glycolysis in erythrocytes and leading to higher glucose utilisation. A comparison is drawn with haemodialysis, where CO2 absorption by the blood similarly enhances glucose metabolism. During haemodialysis, blood glucose levels decrease from an average of 118.3 mg/dL before entering the dialyser to 98.6 mg/dL after passing through, despite the glucose concentration in the dialysate being approximately 105.0 mg/dL.Conclusion CO2 in carbonated water may promote weight loss by enhancing glucose uptake and metabolism in red blood cells. However, the amount is so small that it is difficult to expect weight loss effects solely from the CO2 in carbonated water. Drinking carbonated water may also affect blood glucose measurements. Further studies are needed to explore its long-term effects and potential side effects.